Reparations for Nazi victims in postwar Europe - Ludi, Regula (Cambridge Univ. Press, 2012)
"Reparations of Nazi Victims in Postwar Europe traces reparations back to their origins in the final years of the Second World War, when victims of Nazi persecution for the first time articulated demands for indemnification en masse. Simultaneous appearance of claims in New York, London, Paris and Tel Aviv exemplified the birth of a new standard in political morality. Across Europe, the demand for compensation to individuals who suffered severe harm gained momentum. Despite vast differences in their experiences of mass victimisation, post-war societies developed similar patterns in addressing victims' claims. Regula Ludi chronicles the history of reparations from a comparative and trans-national perspective. This book explores the significance of reparations as a means to provide victims with a language to express their unspeakable suffering in a politically meaningful way"--